2010
DOI: 10.1016/j.rmed.2010.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bone marrow mesenchymal stem cells (BM MSCs) involvement in idiopathic pulmonary fibrosis (IPF)

Abstract: The increased CXCR4 expression by patient MSCs suggests that the BM is probably implicated in the pathophysiology of IPF by mobilizing MSCs in response to or preceding lung injury. The potential role of BM MSCs in IPF is another interesting field for further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 50 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…It is generally agreed that the mechanism of RILI includes radiation-induced injury of parenchymal cells [44], delayed activation of inflammatory reaction [45], and radiation-induced epithelial-mesenchymal transition (EMT) which is reported to mediate pulmonary fibrosis [46]. Therefore, the mechanism of MSC therapy for RILI is considered to regulate the inflammatory response [47-49] and the differentiation of damaged parenchymal cells to promote reconstruction [50]. Recently, some studies revealed the anti-apoptotic function of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that the mechanism of RILI includes radiation-induced injury of parenchymal cells [44], delayed activation of inflammatory reaction [45], and radiation-induced epithelial-mesenchymal transition (EMT) which is reported to mediate pulmonary fibrosis [46]. Therefore, the mechanism of MSC therapy for RILI is considered to regulate the inflammatory response [47-49] and the differentiation of damaged parenchymal cells to promote reconstruction [50]. Recently, some studies revealed the anti-apoptotic function of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that bone marrow-derived circulating progenitor cells could accumulate in the lung and contribute to pulmonary fibrosis after lung injury (2). In experimental pulmonary fibrosis in mice, bone marrow progenitor recruitment accounts for ϳ20% of the fibroblast pool (36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, since vessels express CD34 marker, we cannot assert that CD34 is lost during vessel formation with progenitor cells such as previously described with fibrocytes [55], largely involved in IPF. However, one of the limitation of using CD34 is its widely expression on various other cells such as fibrocytes [55] but also mesenchymal [56], epithelial, and even cancer stem cells [30]. Thus, the use of CD34 as an EPC marker is questionable and the addition of specific markers would be useful to discriminate these different cellular lineages from the putative EPC.…”
Section: Discussionmentioning
confidence: 99%